Answer:
For value of x
x + (2x + 7) + (x - 12 ) = 131
For y
y = 2x + 7
For z
z = x -12
Explanation:
Let three numbers be
x , y and z
Now according to first condition
x + y +z = 131 .......(i)
According to other condition
The second number i.e. y is 7 more then twice of first
which will be
y = 2x + 7 ................(ii)
According to last condition
3rd number i.e. z is 12 less then first which is
z = x - 12 ..................(iii)
As we have got The value of y and z from equation (ii) and (iii) respectively we can find the value of x by substituting these values in equation (i)
Now substituting values of x and y in equation (i) gives us
x + (2x + 7) + (x - 12 ) = 131
From this equation we can find the value of x and which could be substituted to the equation (ii) to find the value of y and for value of z we can substitute it to equation (iii)